La dramatización como estrategia didáctica para una educación holística en el área de lengua y literatura, bloque 6 denominado los cuentos breves para 4to grado de egb de la escuela 25 de diciembre, de la parroquia sucre, de la ciudad de Loja período académico 2015 – 2016 - Iñiguez Ordoñez, Jessica Karina (2017)
The general objective is to contribute with the application of activities that motivate the practice of the dramatization for a holistic education in the area of Language and Literature; The research design is of pre-experimental type; We used the scientific method, statistical, deductive, analytical and synthetic, the techniques was the survey applied to students and guide questions to the teacher; As a result of the research, it is concluded that the theoretical foundation on dramatization as a methodological strategy applied in the workshops, is important to promote holistic education in children, which strengthens academic performance; In this context it is recommended to the teacher to be theoretically based to apply the dramatization; As well as design, plan and implement workshops with diverse strategies through dramatization that allow students to develop a holistic education with rhymes, stories and role play as methodological strategies in the teaching of Language and Literature.